SYSTEMATIC LITERATURE REVIEW: PENGEMBANGAN MEDIA FLIPBOOK INTERAKTIF UNTUK PEMBELAJARAN MEMBACA PEMAHAMAN DI ERA DIGITAL - Mutaqin, Agin Hamdan; Saputra, Dudu Suhandi; Kurino, Yeni Dwi (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
Reading comprehension skills are the foundation of learning, yet they remain a major challenge in Indonesian education, as evidenced by the 2021 PIRLS results, which ranked Indonesia at the bottom. The digital age demands a transformation in learning that integrates multimedia technology to meet the needs of Generation Z. This study uses the Systematic Literature Review method with the PRISMA guidelines to analyse the characteristics and effectiveness of interactive flipbooks in reading comprehension learning. The literature analysis indicates that interactive flipbooks have a pedagogical design that aligns with modern learning needs by coherently integrating text, audio, visuals, and interactive elements. This medium has been proven to enhance text comprehension and student motivation and provide ease of access for flexible learning. Interactive flipbooks serve as a practical solution supporting the development of 21st-century skills and student-centred learning in the digital age.